Autonomy as mode of inclusion and participation of distinct communities and persons belonging to them - Žagar, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2018)
The article as introduction to the following articles on (minority) autonomies suggests autonomies might be tools of diversity management that can contribute to peace and stability in contemporary societies, to inclusion, integration and participation of ethnic, national and other minorities as well as persons belonging to them. The case of Catalonia in Spain serves as context for discussion on socially relevant diversities and divisions in contemporary societies, approaches to, concepts and strategies of regulation and management of diversities and autonomy; it pays special attention to ethnic, cultural and linguistic pluralities, diversities and divisions. Articles that constitute a thematic section of the Journal discuss autonomies as specific approaches, concepts, forms, models, policies and practices for development and implementation of holistic and sustainable strategies for regulation and management of socially relevant diversities in contemporary societies.
Keywords: avtonomija; nacionalna država; narodne manjšine; pluralna družba; upravljanje različnosti; varstvo manjšin